Enhanced tumor penetration for efficient chemotherapy by a magnetothermally sensitive micelle combined with magnetic targeting and magnetic hyperthermia - Wang, Yu; Wang, Rui; Chen, Lixin; Chen, Lili; Zheng, Yi; Xin, Yuanrong; Zhou, Xiqiu; Song, Xiaoyun; Zheng, Jinzhou (Frontiers in Pharmacology, 2022)
A contradiction of nanomedicine existed in high accumulation and poor penetration of nanocarrier in tumor, resulting into low efficacy of chemotherapy. Inspirited by positive effect of hyperthermia on drug diffusion in vivo, we designed a magnetothermally-sensitive micelle (MTM) by integrating magnetic targeting (MT), magnetic hyperthermia (MH) and magnetothermally-responsive drug release to facilitate drug accumulation and penetration in tumor simultaneously. In the study, we synthesized Cyanine7 modified thermosensitive polymer with phase-transition temperature at 42.3 oC, and utilized it to prepare drug loaded MTM by encapsulating superparamagnetic nanoparticles MnFe2O4 and Doxorubicin (DOX). The obtained DOX-MTM did not only show high contents of DOX (9.1%) and MnFe2O4 (38.7%), but also exhibit some advantages on superparamagnetism, high saturation magnetization, excellent magnetocaloric effect, and magnetothermal-dependent drug release. Therefore, the DOX-MTM improved DOX cytotoxicity in vitro by enhancing DOX endocytosis under assistance of MH. Furthermore, the DOX-MTM accumulation and DOX penetration in tumor was enhanced by MT and MH respectively in vivo, resulting in high tumor growth inhibition (84%) and excellent biosafety. According to these results, the study presented an optimizing drug delivery with MH and MH dependent drug release, opening up a feasible strategy to enhance application prospect of nanomedicine in tumor chemotherapy.